Interannual variability of tropospheric trace gases and aerosols: The role of biomass burning emissions - Voulgarakis,A; Marlier,ME; Faluvegi,G; Shindell,DT; Tsigaridis,K; Mangeon,S (Journal of Geophysical Research: Atmospheres, 2015)
Fires are responsible for a range of gaseous and aerosol emissions. However, their influence onthe interannual variability of atmospheric trace gases and aerosols has not been systematically investigatedfrom a global perspective. We examine biomass burning emissions as a driver of interannual variability oflarge-scale abundances of short-lived constituents such as carbon monoxide (CO), hydroxyl radicals (OH),ozone, and aerosols using the Goddard Institute for Space Studies ModelE composition-climate model and arange of observations, with an emphasis on satellite information. Our model captures the observed variabilityof the constituents examined in most cases, but with substantial underestimates in boreal regions. Thestrongest interannual variability on a global scale is found for carbon monoxide (~10% for its global annualburden), while the lowest is found for tropospheric ozone (~1% for its global annual burden). Regionally,aerosol optical depth shows the largest variability which exceeds 50%. Areas of strong variability of bothaerosols and CO include the tropical land regions (especially Equatorial Asia and South America) and northernhigh latitudes, while even regions in the northern midlatitudes experience substantial interannual variability ofaerosols. Ozone variability peaks over equatorial Asia in boreal autumn, partly due to varying biomass burningemissions, and over the western and central Pacific in the rest of the year, mainly due to meteorologicalfluctuations. We find that biomass burning emissions are almost entirely responsible for global CO interannualvariability, and similarly important for OH variability. The same is true for global and regional aerosol variability,especially when not taking into account dust and sea-salt particles. We show that important implications canarise from such interannual influences for regional climate and air quality